Soluções preliminares para missões espaciais no sistema Terra-Lua - Oliveira, Antonio Lucas de (2021)
The aim of this work was to estimate the energy consumption needed for different mission profiles in the Earth-Moon system, using the mathematical framework provided by the Planar Circular Restricted Three-Body Problem (PCR3BP). Starting with the detection of transit-type trajectories in this model, boundary conditions to solve the PR3CCP by means of a Boundary Value Problem were determined. Then, using a transformation of variables and considering the Two-Body Model, portions of the solutions were approximated by oscillating ellipses. Finally, velocity increments to performe orbital maneuvers were estimated, considering three mission profiles. The preliminary results are satisfactory and consistent with those found in the literature. However, further investigation is needed to validate the proposed methodology. Astrodynamics, Orbits, Many-body problem.